Implementation of federal character policy in Nigeria civil service - Onomisi, Timothy; Ku Samsu, Ku Hasnita; Ismail, Mohd Mahadee; Wan Mohd Nor, Murni (International Journal of Recent Technology and Engineering, 2019)
Disturbed with the disparity in the employment distribution in the civil service, the Nigerian government enacted the Federal Character Policy to ensure equality in employment distribution in the country’s civil service. Unfortunately, the policy appears to be unsuccessful in its implementation because disparity still characterizes employment distribution in the Nigerian civil service. This has led to the rivalry, disharmony, and discontent in the service. This paper explores measure aimed at ensuring implementation of the Federal Character Policy in the Nigerian civil service employment distribution. In order to meet the objective of the paper qualitative research method adopted while purposive sampling used in selecting the informants interviewed while the relevant document was equally analyzed. Interpretative Phenomenological Analysis was adopted for data analysis. The paper found that the implementation of the policy can be ensured with committed leadership, orientation and training. The paper provided valuable strategies that will ensure the implementation of the Federal Character Policy in the Nigerian civil service employment distribution and importantly it provided helpful insight for policies that are facing similar implementation setback.